1989
DOI: 10.1002/bdd.2510100407
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of lisinopril (IV/PO) in healthy volunteers

Abstract: When three intravenous doses of lisinopril were administered to healthy volunteers, area under the curve (to infinity) vs dose was linear with a positive intercept. Subtracting area under the extrapolated terminal phase of the serum profile from zero to infinity retained the linear relationship, but shifted the regression line to a zero intercept. It is postulated that the terminal phase reflects binding of drug to angiotensin-converting enzyme (ACE). The half-life for the terminal phase (approximately 40 h) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 9 publications
3
29
0
Order By: Relevance
“…In a previous study in which eight healthy adults were given daily doses of 20 mg lisinopril for 10 days, the mean AUC 0-24 h was 493.5 ng·h/mL, and the mean AUC 0-24 h per 1.0 mg/m 2 was 93.3 ng·h/mL. The mean daily dose in adults in this previous study (adjusted to simulate a 10-mg dose) was 0.14 mg/kg; the mean C max was 82 ng/mL [23]. If this number is divided by 2 to simulate a 10-mg dose, the resulting mean C max is 41 ng/mL; the mean C max per 0.15 mg/kg was 43.5 ng/mL, and mean C max per 1.0 mg/m 2 was 7.8 ng/mL.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study in which eight healthy adults were given daily doses of 20 mg lisinopril for 10 days, the mean AUC 0-24 h was 493.5 ng·h/mL, and the mean AUC 0-24 h per 1.0 mg/m 2 was 93.3 ng·h/mL. The mean daily dose in adults in this previous study (adjusted to simulate a 10-mg dose) was 0.14 mg/kg; the mean C max was 82 ng/mL [23]. If this number is divided by 2 to simulate a 10-mg dose, the resulting mean C max is 41 ng/mL; the mean C max per 0.15 mg/kg was 43.5 ng/mL, and mean C max per 1.0 mg/m 2 was 7.8 ng/mL.…”
Section: Discussionmentioning
confidence: 98%
“…The profiles of serum concentrationtime curves are similar to saturation curves indicating that the first portion of the absorbed substance may accumulate in a blood compartment which is not notably involved in elimination processes. In previous investigations Beermann et al [23,24] suggested that this compartment may be equivalent with binding to serum ACE (about 3 mol. kl).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study in which a single 10 mg oral dose of lisinopril was given to normal subjects (Ulm et al, 1982) and a study in which a 5 mg dose of lisinopril was given as an intravenous bolus in normal subjects (Beermann et al, 1986(Beermann et al, , 1988 serve as a basis of comparison for the results obtained in this study in patients with congestive heart failure (CHF), although statistical comparisons across studies are not appropriate. Essentially all of the dose is recovered in the urine when lisinopril is administered intravenously to normal subjects and patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Given the observed increase in AUC for intravenously '.7: Figure 3 Mean serum concentrations of lisinopril following a 10 mg oral dose in normal subjects (Ulm et al, 1982) (o) and in patients with congestive heart failure (e) (n = 12). As with enalaprilat (Till et al, , 1984 it has been postulated that the terminal phase of the lisinopril serum concentration profile reflects nonlinear binding of lisinopril to angiotensin converting enzyme (Beermann et al, 1986). The contribution of a nonlinear binding component to lisinopril serum profiles precludes conventional model-dependent and model-independent calculations of such parameters as apparent volume of distribution, clearance and serum half-life unless the serum data can be appropriately corrected for this binding.…”
Section: Discussionmentioning
confidence: 99%